Atazanavir–bilirubin interaction: a pharmacokinetic–pharmacodynamic model [Corrigendum] - Lozano R (Dove Medical Press, 2013)
Lozano R, Domeque N, Apesteguia AF. Clinical Pharmacology: Advances and Applications. 2013;5(1):153–159. On page 155, "Deriving Michaelis–Menten’s equation,26 View original paper by Lozano R, Domeque N, Apesteguia AF